Detection of Inguinal Hernia in Patients with Groin Pain on Ultrasound - Muhammad Arif Afridi; Imran Khan; Adnan Ahmed; Ibrar Ahmad; Mehmood Khan; Malik Mairaj Khalid (University of Lahore, 2024)
Objective: To establish ultrasound's contribution to precise diagnosis and to differentiate between inguinal hernia from other diseases in patients with groin pain. Methodology: This descriptive cross-sectional study was conducted in Hayatabad Medical Complex, Peshawar from January to June 2023, with permission of Research Board Ethics Committee. The inclusion criteria comprised patients of all ages and genders with right or left lower quadrant pain suspected of having a hernia. Exclusion criteria included patients who had undergone other ultrasound examinations for lower quadrant pain, diagnosed male prostatic pain, and pregnant women with groin pain. Data collection involved the use of a self-structured questionnaire after obtaining ethical approval and informed consent.The collected data was analysed using SPSS version 25. Descriptive statistics, including frequencies, percentages, mean, and standard deviations, were used to present the data. Results: A total of 323 patients were presented with groin pain and swelling. Out of 323 patients 280 (86.7%) were male patients and 43 (13.3%) were females patients included in our study. All of 323 patients 267 patients were evaluated for inguinal hernia by ultrasound examination during the study period. Out of 323 patients 56 patients of ultrasonographic examinations shows other diseases of groin region which includes 40 patients (12.4%) of enlarged lymph nodes, 10 patients (3.1%) were mass and 6 patients (1.9%) were abscess noted. Thus, ultrasound diagnosed accurately inguinal hernia detection and differentiated us inguinal hernia from other diseases in patients with groin region pain or swelling. Conclusion: Routine Ultrasonography is a helpful and accurate imaging modality performed before general surgery to identify inguinal hernias in groin discomfort patients or swelling.